The Influence of The Role of Internal Audit on Fraud Prevention in The Government of Prabumulih City (Study at the Prabumulih City Inspectorate) - Adinda Ariska; Chairani Adelina; Rika Fitri Ramayani (Siber Nusantara of Economic and Finance Review, 2026)
This study aims to determine the influence of internal audit on fraud prevention in the Prabumulih City Government. The study was conducted at the Prabumulih City Inspectorate. The research method used was quantitative. The sampling technique used saturated sampling, with 66 respondents. Data collection was conducted by distributing questionnaires to respondents, while data analysis used SPSS version 27 statistical software, with stages of validity testing, reliability testing, classical assumption testing, and hypothesis testing. The results showed that the role of internal audit has a positive and significant effect on fraud prevention. This is evidenced by the calculated t-value of 16.442 and a significance level of less than 0.001, which is smaller than 0.05. Thus, the hypothesis in this study is accepted, meaning that the better the role of internal audit, the more effective fraud prevention efforts will be at the Prabumulih City Inspectorate.